The perceptions of the youth generation regarding the 'Buya Hamka' movie - Guntur Bayu Taufiqqurahman; Dani Fadillah; Wiwiek Afifah (International Journal of Visual and Performing Arts, 2023)
This study endeavors to assess and determine the perceptions of the Muhammadiyah youth cohort in the specified Yogyakarta region regarding the movie "Buya Hamka." The rationale behind this research lies in acknowledging film not solely as a source of entertainment but also as a vehicle for imparting knowledge. Buya Hamka, being an eminent national figure, merits emulation by contemporary Indonesians, particularly due to his sacrificial endeavors and unwavering dedication to the nation. Furthermore, as a Muhammadiyah luminary originating from West Sumatra, the youth within the Muhammadiyah movement should be encouraged to draw inspiration from his struggles. Employing a quantitative methodology, this research entails the distribution of questionnaires to respondents belonging to the Muhammadiyah youth cohort in the specific Yogyakarta region. These questionnaires encompass various inquiries designed to gauge their perceptions regarding the Buya Hamka film. The collected data is subsequently processed using the SPSS (Statistical Program for Social Science) application. Through the analysis of this processed data, the researchers have elucidated the viewpoints of the Muhammadiyah youth generation toward the film "Buya Hamka". The findings of this investigation underscore a correlation between the aspirations of the younger demographic for experiencing high-caliber content centered on inspirational narratives derived from national figures. This correlation is directly evident in their viewing patterns, as inferred from the SPSS data analysis articulated in the study. It demonstrates a discernible awareness among the younger generation regarding films that depict the inspiring stories of national figures, reflected in their viewing habits and the subsequent impact on those who feel inspired after watching the film, especially when the theme revolves around Buya Hamka's struggle.